Tele-genetic versus onsite counseling for APOE disclosure: a 6-month study of empowerment, psychological distress, and behavioral outcomes in cognitively diverse individuals - Makri, Marina; Angelidou, Ioanna A.; Moraitou, Despoina; Fidani, Liana; Tegos, Thomas; Kimiskidis, Vasileios; Tsolaki, Magdalini (The journal of gene medicine, 2025)
Background With the increasing demand for clinical genetic services and the lack of clinical geneticists, tele-genetics is utilized in clinical genetics to improve cost efficiency and equitable access to health services. But is tele-genetic counseling (GC) for APOE genotype disclosure for Alzheimer's disease (ad) risk as effective as onsite interventions? This study examines behavioral, psychological, empowerment, and risk recall responses following the disclosure of genetic results of AD risk to first-degree relatives of people with AD (PwAD) in Greece. Materials and Methods Participants (N = 93) were randomly assigned to one of two GC interventions. Additional grouping variables included the cognitive status (healthy relatives of PwAD or people with mild cognitive impairment [MCI]) and the genetic test result (ε4-positive or not). Throughout the three time points (baseline/before GC, 3 and 6 months post-disclosure), participants completed questionnaires for psychological well-being, empowerment, risk recall, and behavioral adaptations. Repeated-measures ANOVA, Mann-Whitney U tests, logistic regression, Friedman test, and χ2 tests were used to examine changes in different scores. Results Ninety-three adults (mean age 64.77 years, years of education 13.72, 61% female) were randomly assigned to online (46 participants) and onsite (47 participants) groups. There were no statistically significant differences between the two intervention groups in psychological and empowerment scores. However, people with MCI have substantially lower odds of recalling risk after 6 months and lower empowerment scores. People with ε4 were much more likely to endorse behavior change and indicated higher distress scores. Conclusion Tele-GC can serve as an effective intervention for APOE disclosure for healthy relatives of PwAD and people with MCI.